2018
DOI: 10.1519/jpt.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Dry Needling on the Infraspinatus Latent and Active Myofascial Trigger Points in Older Adults With Nonspecific Shoulder Pain: A Randomized Clinical Trial

Abstract: Background and Purpose:Shoulder pain is a prevalent condition in older adults. Some authors associate nonspecific shoulder pain with myofascial trigger points (MTrPs) in the infraspinatus muscle. Dry needling is recommended to relieve the MTrP pain of shoulders in the short term (<9 days). Active MTrPs dry needling improves shoulder pain and the irritability of the satellite MTrPs in the referred pain area. Nociceptive activity at a latent MTrP may influence motor activity and the sensitivity of MTrPs in dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 50 publications
3
65
1
3
Order By: Relevance
“…For the control group, these latent MTrPs were situated bilateral in both non-painful shoulders. Shoulder pain was considered if there was pain at rest and mainly located in the glenohumeral joint between the acromion, the insertion of the deltoid muscle, and the lateral region of the scapula (Calvo, Pacheco & Hita, 2015; Calvo-Lobo et al, 2016). Non-specific shoulder pain was considered if a previous diagnosis was not present in the medical record considering structural, neurological, visceral or red flag conditions (Mitchell et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the control group, these latent MTrPs were situated bilateral in both non-painful shoulders. Shoulder pain was considered if there was pain at rest and mainly located in the glenohumeral joint between the acromion, the insertion of the deltoid muscle, and the lateral region of the scapula (Calvo, Pacheco & Hita, 2015; Calvo-Lobo et al, 2016). Non-specific shoulder pain was considered if a previous diagnosis was not present in the medical record considering structural, neurological, visceral or red flag conditions (Mitchell et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…New treatments strategies for older adults with symptomatic shoulders are necessary (Burner et al, 2014). Therefore, non-specific shoulder pain is associated with myofascial pain syndrome (MPS), and treatment can reduce pain intensity, increase pressure pain threshold (PPT) and modify grip strength in the upper limbs of older adults (Calvo, Pacheco & Hita, 2015; Calvo-Lobo et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive acetylcholine maintains a sustained depolarization of the post junctional membrane, which in turn results in an excessive release of calcium from the sarcoplasmic reticulum and sustained sarcomeres' contractions. Studies also suggested that an impaired re-uptake of calcium into the sarcoplasmic reticulum induced by calcium channel blockers may cause MTrPs 8,9 .…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Superficial dry needling, which involves placing an acupuncture needle in the skin overlying an MTrPs and electrical twitch-obtaining intramuscular stimulation 21,24 .Based on previous infraspinatus studies, Trp-DN produces segmental anti nociceptive effects. On the one hand, active MTrPs-DN improves shoulder pain and the irritability of the satellite MTrPs in the referred pain area 8,25 . For patients with myofascial pain syndrome of the infraspinatus muscle and shoulder pain, dry needling of trigger points of that muscle showed an immediate reduction of pain and improvement of range of movement 26 .…”
Section: Diagnosis:-mentioning
confidence: 99%